Evaluasi Layanan Jalur Sepeda pada Rute Jalan Ryacudu Kota Bandarlampung - Rio Abdullah Romadhon; Haris Murwadi (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2023)
The City Government of Bandar Lampung has made several routes for bicycle lanes including the Jalan Ryacudu Route. This path is quite busy used by cyclists for their various purposes. This study aims to determine the dominant factor in the level of satisfaction with bicycle lane services and to determine differences in levels of community satisfaction regarding bicycle lane services on the Ryacudu Road route. The method used in this research is descriptive quantitative method. Data collection was carried out through a closed questionnaire on 441 respondents. The data were analyzed using distribution analysis, analysis and analysis of variance (ANOVA). The results showed that 1) the dominant variables that influence the evaluation of bicycle lane services include: lane arrangement (3.95), convenience from traffic (3.91), and comfort in bicycle lane conditions (3.87). 2) The difference in the level of significant satisfaction occurs in the mileage variable. Medium mileage (5-10 and 11-15) tends to have a high level of satisfaction.